2016
DOI: 10.1016/j.techsoc.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Roadblocks to responsible innovation: Exploring technology assessment and adoption in U.S. public highway construction

Abstract: U.S. Public Highway Construction Industry professionals are responsible for assessing and adopting new technology that can improve the cost and quality of roadways. This paper investigates features of the technology assessment and adoption process in the U.S. public highway construction industry that both facilitate and hinder responsible innovation. Often technological innovations are incongruent with current specifications, i.e., regulatory construction standards, whereby specification reform serves as a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…A process broker typically has thorough knowledge of the institutional system. She can use this knowledge to act as a gatekeeper (Kimmel, Toohey, & Delborne, 2016), enhance democracy and solicit public participation in policymaking (Gilad & Alon-Barkat, 2018;Nelson & Svara, 2015), manipulate rules to push a policy proposal (Zahariadis & Exadaktylos, 2016), de-escalate conflict and prevent coalitions from blocking policy decisions (Ingold & Varone, 2011), or institutionalize ideas and avoid policy reversal (Meijerink & Huitema, 2010). In the absence of a clear policy direction, she can also steer the policy from a statement of intent to an implementation plan by facilitating learning about various alternatives, or by driving her own agenda (Meijerink & Huitema, 2010;Pedersen, Hjelmar, & Bhatti, 2018).…”
Section: Process Brokermentioning
confidence: 99%
“…A process broker typically has thorough knowledge of the institutional system. She can use this knowledge to act as a gatekeeper (Kimmel, Toohey, & Delborne, 2016), enhance democracy and solicit public participation in policymaking (Gilad & Alon-Barkat, 2018;Nelson & Svara, 2015), manipulate rules to push a policy proposal (Zahariadis & Exadaktylos, 2016), de-escalate conflict and prevent coalitions from blocking policy decisions (Ingold & Varone, 2011), or institutionalize ideas and avoid policy reversal (Meijerink & Huitema, 2010). In the absence of a clear policy direction, she can also steer the policy from a statement of intent to an implementation plan by facilitating learning about various alternatives, or by driving her own agenda (Meijerink & Huitema, 2010;Pedersen, Hjelmar, & Bhatti, 2018).…”
Section: Process Brokermentioning
confidence: 99%
“…The main characteristics of the Generation Z discussed in the previous section have pointed out that in case of applying science education in practice, we should not think of classic classroom teaching and traditional classroom solutions only but more modern techniques, too. In order to address this challenge, we analyzed the methods that were used to incorporate RRI thoughts into practice (see, e.g., Arentshorst, de Cock Buning, & Broerse, 2016;Deák & Lukovics, 2014;Fisher, 2007;Flipse & Osseweijer, 2013;Imreh-Tóth & Imreh, 2014;Kimmel, Toohey, & Delborne, 2016;Okada, 2016;Panzda & Ellwood, 2013;Pavie & Carthy, 2014;Ravesteijn, Liu, & Yan, 2015;Schuurbiers, 2011). We found that the methodological logic of Socio-Technical Integration Research (STIR) method seems to be a good solution, though it has been tested only among active researchers.…”
Section: Socio-technical Integration Among Potential Scientistsmentioning
confidence: 99%
“…Ethics and ideology are interconnected and many ethical issues of our time are inevitably developed from and around ideological values [55,56]. The discussion of ideology in RRI is scattered throughout the sample and is mostly found in the context of engagement, as actors or stakeholders involved in participatory action either potentially carry ideological biases that contribute to the low productivity of engagement practices [18,57], or can be infected by the ideological aims of RRI [13]. Also, risk and scenario anticipation, namely in fields of emerging science and technology with high uncertainty levels, appear to be rich in ideological visions of the future [15,17].…”
Section: Accepted Manuscriptmentioning
confidence: 99%